DETERMINASI HARGA-HARGA SAHAM BERDASARKAN FUNDAMENTAL FAKTOR - Arnanda Ajisaputra (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study aims to determine the effect of stock price movements on EPS, PBV, and DER on shares indexed by JII during 2014 s.d. 2018. The research method uses the Quantitative Multiple Linear Regression Model. To take a sample from the population used purposive sampling method. The results obtained were 15 issuers indexed by JII continuously during 2015 s.d. 2018. Of the fifteen issuers, they have EPS, PBV, and DER which simultaneously affect their stocks price movements by 87.4%, while 12.6% is influenced by other factors. Partially, EPS has a significant and positive effect on stock prices, PBV also has a significant and positive effect on stock prices, but DER has a significant and negative effect on stock prices. Keywords: JII, EPS, PBV, DER, stock price